2015
DOI: 10.1155/2015/189694
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Smoking Cessation with Acupuncture in a Hong Kong Population

Abstract: Background. Observational studies of smoking cessation with acupuncture have been reported widely; however, few researchers have focused on its predictors. Objective. This paper attempts to explore the predictors for smoking cessation with acupuncture in a Hong Kong population, aiming to provide references for clinical treatment in the future. Methods. We performed a secondary analysis of data from our observational study “Acupuncture for Smoking Cessation (2011–2014)” in Hong Kong. A total of 23 indexes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Unfortunately, a high drop-out was still inevitable, indicating that the effects of acupuncture on smoking cessation may be related to personal environment and living factors [26]. It was worthy of more attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a high drop-out was still inevitable, indicating that the effects of acupuncture on smoking cessation may be related to personal environment and living factors [26]. It was worthy of more attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Various therapeutic approaches, including acupuncture, have been used to help people quit smoking. In Hong Kong, a free community-based smoking cessation service combining acupuncture and auricular acupressure has been provided since 2010, with positive results [ 8 , 12 , 33 ]. Our findings from the Hong Kong site in this Guangdong-Hong Kong-Macau Greater Bay Area project provide updated and additional evidence on the effects and safety of combined acupuncture and auricular acupressure for smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…The major aim of our study was to investigate the success rates of smoking cessation posttreatment. It has been reported that receiving sufficient and qualified acupuncture is a leading factor for short-term smoking cessation [ 33 ]. The more acupuncture treatment received, the greater the possibility of quitting tobacco dependence with acupuncture [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various therapeutic approaches, including acupuncture, have been used to help quit smoking. In Hong Kong, a pilot project was launched since 2010 to provide free acupuncture for smoking cessation with positive results [8, 12,33]. The ndings from the Hong Kong site in this Guangdong-Hong Kong-Macau Greater Bay Area Project gave an update and additional evidence on the e cacy and safety of acupuncture for smoking cessation in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that receiving su cient and quali ed acupuncture is the leading factor for short-term smoking cessation. The more acupuncture treatment received, the greater the possibility of quitting tobacco dependence with acupuncture [33]. A previous clinical trial in Norway reported that six acupuncture sessions may help motivate smokers to quit smoking completely, and the effect may last for ve years [10].…”
Section: Strengths Limitations Of Studymentioning
confidence: 99%